Budget support to the health sector—The right choice for strong institutions? Evidence from panel data - Tim Röthel (Review of Development Economics, 2022)
This article examines the relationship of sector budget support to the health sector and the infant mortality rate for developing countries. Project-type interventions have been widely used in developing countries in the past decades. These smaller-scale interventions often did not bring the results that the donors would have wanted, at least on a macro level. At the beginning of the millennium, forums on aid effectiveness proposed new principles to increase the effectiveness of aid. Many scholars agreed that one of the answers would be budget support. This article tries to answer whether budget support is the efficient aid modality in countries with strong institutions. In the baseline scenario, a panel data analysis is applied, which includes 113 countries between 2010 and 2018. This dynamic linear panel model is estimated by using ordinary least squares (OLS) and system generalized method of moments (GMM). Health sector aid, in general, has a significant and negative effect on the infant mortality rate in the average country. Sector budget support is insignificant in the baseline estimation and when interacted with a governance variable. In contrast, project-type interventions exhibit significant and negative effects on the outcome variable. The results indicate that sector budget support might not be the superior choice among the aid modalities in the health sector, even in countries with good governance.
Keywords: 330; development; development policy; health; mortality; official development assistance